PENGARUH MOTIVASI TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI NEGERI SIPIL (PNS) DI SEKOLAH TINGGI PARIWISATA NUSA DUA BALI - Juniari, Ni Kadek Eni; Riana, I Gede; Subudi, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.11.TAHUN 2015, 2016)
The aims of this study ar e to analyze the effect of motivation on job satisfaction, on employee performance, and to analyze the effect of job satisfaction on employee performance. Population on this research is all the civil servants at Bali Tourism Institute Nusa Dua, Bali, which used 74 respondents which were selected as sample by simple random sampling technique. Data were collected through questionnaires distributed to respondents then analyzed using descriptive analyze and Partial Least Square (PLS). The results of the study showed that a) motivation gives positive and significant impact on job satisfaction, b) motivation give positive and significant impact on employee performance, c) job satisfaction give positive and significant impact on employee performance. The implication of this research is that with the appreciation and recognition of the work and supported by a fair system of supervision would be able to increase employee motivation and drive the spirit to finish the job, so it will be able to improve the performance of employees in terms of both quality and quantity. Keywords : Motivation, Job Satisfaction, Employee Performance